APPLICATION OF LETHAL OVITAP AS A MEDIA FOR CONTROLLING DHF LARGE VECTORS IN THE WORKING AREA OF SUKARAMI HEALTH CENTER, PALEMBANG CITY IN 2022 - Priyadi, Priyadi; Kamsul, Kamsul (LPPM Univ. Ibn Khaldun Bogor, 2023)
The Mosquito Nest Eradication Program (PSN) is currently not optimally implemented in controlling Dengue Fever vectors, so an alternative strategy is needed to overcome it, especially in the working area of ​​the Sukarami Health Center which has an incidence rate of Dengue Fever in 2022 of 21 cases with 2 deaths. One of the efforts carried out is a community-based larval survey that is sustainable with efforts to apply lethal ovitrap which can inhibit and break the developmental phase of the larvae. Activities carried out in the form of practice on how to make lethal ovitrap to cadres of larva monitors and the community directly. The larva monitors as an extension of the sanitarian/sanitation officer were given instructions on how to make lethal ovitrap, after which lethal ovitrap was made for the community whose family members were positive for Dengue Hemorrhagic Fever and the community around the house with a target of 105 houses with 10 jumantik and 2 lecturers as community administrators. and 10 students. From this activity, cadres of larva monitoring (jumantik) and the community were able to make lethal ovitrap and there was an increase in the larva-free rate (ABJ) after the application of lethal ovitrap which would reduce the breeding potential of Aedes aegypti mosquitoes in the larval phase. The results that have been achieved are 105 households surveyed by larvae and the practice of making lethal ovitrap by the community and cadres of larva monitors as an alternative effort in controlling larvae which can increase the larvae-free rate in the Sukarami Palembang Health Center area from 92.5% to 95%.